Alkali-silica reactivity of basaltic aggregates of Mesopotamia Argentina: case studies - Madsen, Lenis (2019)
This work consists of two stages; first, studies were conducted to evaluate the potential reactivity of crushed material (6–20 mm fraction) from two quarries (named A and B) producing basaltic aggregates in the northeast of Argentina (Mesopotamia region, province of Corrientes). The studies included petrographic analysis, identification of expandable clay by X-ray diffraction, and standardized physical tests on mortar bars and concrete prisms to evaluate their potential reactivity. Also, dissolved silica was determined according to the chemical test method. Although the studied aggregates cannot be qualified in the same way based on the results of the physical tests, there is a direct relationship between the glass and expandable clay content in the samples (quarry A aggregate > quarry B aggregate) and their behavior in the physical and chemical tests (higher values for aggregates A). In the second stage, two structures of the province of Corrientes were studied: an urban pavement (made with aggregate A) and an airport runway (made with aggregate B), both with signs of alkali-silica reaction (ASR). A visual survey was carried out and concrete cores were extracted. On the latter, physical tests, petrographic studies, and SEM-EDS determinations were performed to identify reaction products. In the urban pavement, aggregate A, used as coarse aggregate, and the presence of siliceous sandstones rich in chalcedony and microcrystalline quartz in the fine aggregate would have contributed to ASR development, while in the airport runway, the initial deterioration would have favored the ASR as a secondary process.